2022
DOI: 10.3389/fonc.2022.903231
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical resection and radiofrequency ablation for stages I and II elderly hepatocellular carcinoma patients (≥ 65 years): A SEER population-based propensity score matching’s study

Abstract: ObjectivesThe treatment for hepatocellular carcinoma (HCC) remains controversial and limited in elderly patients. Therefore, we aimed to explore treatment choices for the elderly patients (≥ 65years) following surgical resection (SR) versus radiofrequency ablation (RFA) with HCC (single lesion less than 5 cm).MethodsWe used SEER database to identify HCC patients who received treatment of SR/RFA. Kaplan–Meier method and Cox proportional hazards regression method were used to determine the prognostic factors ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Reviewing the literature, we found no prior landmark analyses of the risk of recurrence or of death without recurrence following curative-intent treatments for HCC. However, 5 prior studies have conducted survival landmark analyses following resection, [16][17][18][19][20] and one of these studies also presented landmark analyses following ablation. [20] The patient populations in the 5 studies differ substantially in geography, HCC stage, HCC grade, cirrhosis, tumor size, and microvascular invasion, complicating attempts to compare their results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviewing the literature, we found no prior landmark analyses of the risk of recurrence or of death without recurrence following curative-intent treatments for HCC. However, 5 prior studies have conducted survival landmark analyses following resection, [16][17][18][19][20] and one of these studies also presented landmark analyses following ablation. [20] The patient populations in the 5 studies differ substantially in geography, HCC stage, HCC grade, cirrhosis, tumor size, and microvascular invasion, complicating attempts to compare their results.…”
Section: Discussionmentioning
confidence: 99%
“…However, 5 prior studies have conducted survival landmark analyses following resection, [16][17][18][19][20] and one of these studies also presented landmark analyses following ablation. [20] The patient populations in the 5 studies differ substantially in geography, HCC stage, HCC grade, cirrhosis, tumor size, and microvascular invasion, complicating attempts to compare their results. With that caveat in mind, the existing literature generally indicates a stable survival over the landmarks following both resection and ablation, and that is consistent with what we show in Figure 2 (bottom) and Supplemental Figure S1, http://links.lww.com/HC9/A939.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor size is a significant factor that influences the prognosis of hepatocellular carcinoma (HCC), and it is commonly used as a crucial criterion for HCC staging and treatment guidelines [24]. Several multicenter studies focusing on surgically-resected HCC have consistently demonstrated that tumors measuring >5 cm are associated with a poorer prognosis than those measuring ≤5 cm [25][26][27]. The nomogram clearly illustrates the rela-tionship between the tumor size and prognosis, indicating that as the tumor size increases, the corresponding score also increases, indicating a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%